2015
DOI: 10.1186/s12871-015-0073-1
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy in intensive care unit patients can be performed without bleeding complications in case of normal thromboelastometry results (EXTEM CT) despite increased PT-INR: a prospective pilot study

Abstract: BackgroundCoagulopathy is often accompanied by prolongation of prothrombin time (PT) in septic and nonseptic patients in intensive care unit (ICU). The conventional way to correct the coagulopathy is to administer fresh frozen plasma (FFP) before invasive procedures to minimise the risk of bleeding. However, prolonged PT can be present even in hypercoagulation status, resulting in unnecessary administration of FFP. In the present study, we have assessed the reliability of thromboelastometry in case of prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…A prospective study of 119 intensive care patients undergoing tracheostomy demonstrated no difference in bleeding between patients with INR of ≤ 1Á2 or 1Á3-1Á84. These patients also had thromboelastometry profiles carried out with results being within the normal range in all cases except one (Durila et al, 2015).…”
Section: Abnormal Clotting Tests In the Absence Of Bleedingmentioning
confidence: 97%
“…A prospective study of 119 intensive care patients undergoing tracheostomy demonstrated no difference in bleeding between patients with INR of ≤ 1Á2 or 1Á3-1Á84. These patients also had thromboelastometry profiles carried out with results being within the normal range in all cases except one (Durila et al, 2015).…”
Section: Abnormal Clotting Tests In the Absence Of Bleedingmentioning
confidence: 97%
“…147 169 Increasing evidence shows that viscoelastic assays can be used to assess haemostatic status in patients with liver disease, with evidence that this can result in a reduction in blood products transfused. [170][171][172][173][174] This has become increasingly established in liver surgery but more recently for other procedures. In a small randomised trial, De Pietri 175 showed that in patients with cirrhosis and an INR >1.8 and/or platelet count <50×10 9 /L requiring invasive procedures, a thromboelastogram-guided transfusion strategy led to a significantly lower use of blood products (17% compared with 100% transfusion in the standard of care group) without an increase in bleeding complications; only one major bleed occurred, which was in the standard of care group.…”
Section: Coagulation Testingmentioning
confidence: 99%
“…[50][51][52] It has been shown that in septic patients with prolonged prothrombin time but normal or hypercoagulable parameters of viscoelastometric testing, invasive procedures are not associated with an increased bleeding risk. 53,54 This is also reflected by the discordance that has been observed between international normalized ratio and TEG R times in previous studies. 55 Also, both hyperor hypofibrinolysis can be detected by viscoelastometric testing in trauma patients and patients with sepsis, DIC, or liver disease.…”
Section: Assessment Of Prothrombotic Abnormalities and Complex Coagulmentioning
confidence: 80%